Unpacking mental models through laboratory experiments. (April 2016) - Gary, Michael Shayne; Wood, Robert E.
Abstract: This article summarizes the findings from three laboratory studies investigating the content of decision makers' mental models and the relationship between mental models and performance on microworld simulations. We examine three different components of mental models: perceived causal relationships, high‐level strategies, and decision rules. The findings advance our understanding of the effects of different levels of complexity, different causal diagram presentations, and different learning paths on mental models and performance. Copyright © 2017 System Dynamics Society